Uranium-polymetallic mineralization relationship and comprehensive mineralization model in the Xiangshan ore field, South China: constraints from H-O-S-Pb-Sr multi-isotope data - Guo, Jian; Li, Ziying; Nie, Jiangtao; He, Sheng; Wang, Junxian; Khan, Waseem (Frontiers in Earth Science, 2025)
The Xiangshan ore field, recognized as China’s premier volcanic-hosted uranium deposit cluster, has recently revealed significant exploration breakthroughs through the discovery of vertically zoned Pb-Zn-Ag-Cu polymetallic mineralization beneath shallow uranium systems, establishing a characteristic “upper uranium-lower polymetallic” vertical zoning configuration. This distinctive metallogenic architecture has propelled investigations into the genetic connections and superimposed mineralization mechanisms between deep polymetallic systems and surficial uranium enrichment, representing a pivotal frontier for advancing comprehensive evaluation strategies of uranium-polymetallic resources in volcanic terrains. Through systematic comparative analysis of H-O-S-Pb-Sr isotopic signatures across both mineralization types, this study elucidates: (1) Uranium mineralization exhibits significantly higher meteoric water contributions (δ18OH2O: 0.95‰–4.95‰) and crustal material inputs (87Sr/86Sr: 0.71447 to 0.72072; δ34S: 6.2‰–19.55‰) compared to polymetallic counterparts; (2) 206Pb/204Pb, 207Pb/204Pb, and 208Pb/204Pb ratios for sulfide minerals of polymetallic mineralization ranging from 17.599 to 18.262, 15.558 to 15.725, and 37.934 to 38.875 and sample points exhibit a linear distribution pattern imply unique sulfur enrichment processes potentially associated with uranium-rich hydrothermal systems; (3) Multivariate isotopic evidence confirms that uranium and polymetallic mineralization represent products of two discrete metallogenic events under the extensional tectonic regime of South China.